Fiscal harmonization in common markets - Shoup, Carl S.; Columbia University (New York : Columbia University Press, 1967)
The first part of the chapter one is thus an exploration of those parts of the theory of regional disparities most relevant to fiscal harmonization. The second part moves to the specific level, describing action taken in the EEC countries and the United Kingdom on a national level and also the supranational policies on regional disparities adopted by Benelux, the European Coal and steel community, and the EEC itself.
"Study ... initiated in 1962 by the School of International Affairs of Columbia University."
Includes bibliographies.
hza 28/01/2019
Loans
Keywords: International economic integration